Olefin polymer film and preparation method thereof
By polymerizing the olefin polymer film prepared in the presence of a catalyst, the problems of poor processability and insufficient heat sealing of linear low-density polyethylene film are solved, and easy molding of the film and excellent low-temperature heat sealing are achieved.
Patent Information
- Application Number
- CN202080082827.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-28
- Filing Date
- 2020-11-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-20
AI Technical Summary
The linear low-density polyethylene films prepared under the prior art have poor processability and poor heat sealing properties, especially under low temperature conditions.
By polymerizing the olefin monomer in the presence of a catalyst, an olefin polymer film having a density between 0.910 g/cm3 and 0.940 g/cm3, a melt index ratio between 10 and 60, and a comonomer distribution slope of 1 or more was prepared. The film has excellent heat sealing strength under specific conditions, especially at low temperatures.
The olefin polymer film is easy to form, and has excellent mechanical strength and heat sealing properties, especially under low temperature conditions, which is significantly improved.
Smart Images

Figure BDA0003666904770000021 
Figure BDA0003666904770000022 
Figure BDA0003666904770000031
Abstract
Description
Technical Field
[0001] The present invention relates to an olefin polymer film and a preparation method thereof, and more particularly to an olefin polymer film which is easy to form into a film and has excellent heat-sealing strength, especially low-temperature heat-sealing strength, and a preparation method thereof. Background Art
[0002] As a catalyst for olefin polymerization, metallocene catalyst is a compound composed of transition metal or transition metal halide coordinated with ligands such as cyclopentadienyl, indenyl and cycloheptadienyl, and its basic form is a sandwich structure.
[0003] As another catalyst for polymerizing olefins, the Ziegler-Natta catalyst has uneven properties of the active centers because the metal components as active centers are dispersed on an inert solid surface, while the metallocene catalyst is a compound with a fixed structure and is therefore considered to be a single-site catalyst in which all active centers have the same polymerization characteristics. The polymer polymerized under this metallocene catalyst has a narrow molecular weight distribution and a uniform comonomer distribution, and the copolymerization activity is higher than that of the Ziegler-Natta catalyst.
[0004] Among them, linear low-density polyethylene (LLDPE) is made by copolymerizing ethylene and α-olefins under low pressure using a polymerization catalyst, and has a narrow molecular weight distribution and a short chain branch (SCB) of a certain length, and usually has no long chain branch (LCB). In addition to the characteristics of general polyethylene, films made of linear low-density polyethylene also have high tensile strength and elongation, as well as excellent tear strength and impact strength, etc., and are therefore widely used in stretch films and laminated films that are difficult to achieve with low-density polyethylene (LDPE) or high-density polyethylene (HDPE).
[0005] However, linear low-density polyethylene prepared under metallocene catalysts has poor processability due to a narrow molecular weight distribution, and films made therefrom tend to have poor heat-sealing properties.
[0006] Therefore, there is a need for an olefin polymer film that is easy to form into a film and has excellent mechanical strength and heat sealability, especially low-temperature heat sealability. Summary of the invention
[0007] Technical issues
[0008] An object of the present invention is to provide an olefin polymer film, particularly a linear low-density polyethylene film, which is easy to form into a film and has excellent mechanical strength and heat-sealability, especially low-temperature heat-sealability.
[0009] Another object of the present invention is to provide a method for preparing an olefin polymer film, particularly a linear low-density polyethylene film, which is easy to form into a film and has excellent mechanical strength and heat-sealability, especially low-temperature heat-sealability.
[0010] Technical Solution
[0011] In order to achieve the above object, in a specific embodiment, the present invention provides an olefin polymer film, wherein the film is made by molding an olefin polymer, wherein the olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 , preferably 0.910g / cm 3 Up to 0.920g / cm 3 (2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR) is 10 to 60, preferably 20 to 40; and (3) the comonomer distribution slope (comonomer distribution slope; CDS) defined by the following mathematical formula 1 is 1 or more, preferably 2 to 5, and the olefin polymer film has a heat seal strength of 90 gf / 2.5 cm or more, preferably 90 to 200 gf / 2.5 cm, measured at 0.2 bar, 1.5 seconds and 125°C, and a heat seal strength of 210 gf / 2.5 cm or more, preferably 210 to 250 gf / 2.5 cm, measured at 0.2 bar, 1.5 seconds and 140°C.
[0012]
Mathematical formula 1
[0013]
[0014] Among them, C 20 and C 80 are the comonomer contents corresponding to the cumulative weight fractions of 20% and 80% in the comonomer distribution, M 20 and M 80They are the molecular weights corresponding to the cumulative weight fractions of the comonomer distribution reaching 20% and 80%, respectively.
[0015] The olefin polymer may be prepared by polymerizing an olefin monomer in the presence of a catalyst, the catalyst comprising at least one transition metal compound represented by the following Chemical Formula 1 and at least one co-catalyst compound.
[0016]
Chemical formula 1
[0017]
[0018] In the chemical formula 1, n is each independently an integer from 1 to 20,
[0019] M is titanium (Ti), zirconium (Zr) or hafnium (Hf),
[0020] X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, C 6-20 Arylamide or C 1-20 Alkylene,
[0021] R 1 To R 4 and R 5 To R 8 are each independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl,
[0022] R 9 To R 11 and R 12 To R14 are each independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl,
[0023] R 1 To R 4 and R 5 To R 8 Each independently can form a substituted or unsubstituted saturated or unsaturated C 4-20 ring.
[0024] In addition, the co-catalyst compound may be selected from the compound represented by the following Chemical Formula 2, the compound represented by Chemical Formula 3, and the compound represented by Chemical Formula 4.
[0025]
Chemical formula 2
[0026]
[0027]
Chemical formula 3
[0028]
[0029]
Chemical formula 4
[0030] [LH] + [Z(A)4] - or [L] + [Z(A)4] -
[0031] In the chemical formula 2, n is an integer of 2 or more, R a For halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 Hydrocarbon,
[0032] In the chemical formula 3, D is aluminum (Al) or boron (B), R b , R c and Rd are independently a halogen atom, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon or C 1-20 Alkoxy,
[0033] In the chemical formula 4, L is a neutral or cationic Lewis base, [LH] + and [L] + is a Bronsted acid ( nsted acid), Z is a Group 13 element, and A is each independently a substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 alkyl.
[0034] In addition, the catalyst may further comprise a carrier supporting the transition metal compound and the promoter compound.
[0035] Preferably, the olefin polymer is a copolymer of an olefin monomer and an olefin comonomer. Specifically, the olefin monomer is ethylene, and the olefin comonomer is one or more selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene and 1-hexadecene. Preferably, the olefin polymer is a linear low density polyethylene, wherein the olefin monomer is ethylene and the olefin comonomer is 1-hexene.
[0036] Preferably, the olefin polymer film according to a specific embodiment of the present invention has a 95°C hot tack strength of 0.5 N / 2 cm or more, preferably 0.5 to 3.5 N / 2 cm, and a 110°C hot tack strength of 3.5 N / 2 cm or more, preferably 3.5 to 7.5 N / 2 cm.
[0037] Preferably, the haze of the olefin polymer film according to a specific embodiment of the present invention measured after being formed into a thickness of 50 μm may be 10% or less, preferably 7% or less, or 6% or less.
[0038] Specifically, the film according to the specific embodiment of the present invention can be one selected from a stretch film, a laminated film, a plastic film, a silage film, and an agricultural film.
[0039] In another specific embodiment, the present invention provides a method for preparing an olefin polymer film, the method comprising: step (a), polymerizing olefin monomers in the presence of a catalyst comprising at least one transition metal compound represented by the following chemical formula 1 and at least one co-catalyst compound to obtain an olefin polymer; and step (b), molding the olefin polymer to obtain a film, wherein the olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 , preferably 0.910g / cm 3 Up to 0.920g / cm 3 (2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60, preferably 20 to 40; and (3) the comonomer distribution slope (CDS) defined by the following mathematical formula 1 is 1 or more, preferably 2 to 5, the heat sealing strength of the olefin polymer film measured at 0.2 bar, 1.5 seconds and 125°C is 90 gf / 2.5 cm or more, preferably 90 to 200 gf / 2.5 cm, and the heat sealing strength measured at 0.2 bar, 1.5 seconds and 140°C is 210 gf / 2.5 cm or more, preferably 210 to 250 gf / 2.5 cm.
[0040]
Chemical formula 1
[0041]
[0042]
Mathematical formula 1
[0043]
[0044] In the chemical formula 1, n, M, X and R 1 To R 14 , and C in the above mathematical formula 1 20 , C 80 、M 20 and M 80 Same as above definition.
[0045] In the step (a), the polymerization of the olefin monomers may be performed by gas phase polymerization. Specifically, the polymerization of the olefin monomers may be performed in a gas phase fluidized bed reactor.
[0046] In addition, in step (a), the olefin polymer can be prepared by copolymerizing an olefin monomer and an olefin comonomer. In this case, the olefin monomer is ethylene, and the olefin comonomer can be selected from one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene and 1-hexadecene. Preferably, the olefin monomer is ethylene, and the olefin comonomer is 1-hexene.
[0047] The olefin polymer film prepared by the method for preparing an olefin polymer film according to a specific embodiment of the present invention can meet the following requirements: a 95°C hot tack strength of 0.5 N / 2 cm or more, preferably 0.5 to 3.5 N / 2 cm, and a 110°C hot tack strength of 3.5 N / 2 cm or more, preferably 3.5 to 7.5 N / 2 cm.
[0048] Beneficial Effects
[0049] The olefin polymer film according to the specific embodiment of the present invention, especially the linear low-density polyethylene film, is easy to form into a film and has excellent mechanical strength and heat sealing properties, especially low-temperature heat sealing properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A GPC-FTIR chart for describing the measurement method of CDS defined by Mathematical Formula 1 is shown.
[0051] Figures 2 to 4 GPC-FTIR charts for measuring CDS of the olefin polymers of Examples 1 to 3 are shown respectively.
[0052] Figure 5 and Figure 6 GPC-FTIR charts for measuring CDS of the olefin polymers of Comparative Examples 1 and 2 are shown respectively.
[0053] Figure 7 A graph showing the heat seal strength of Example 1, Comparative Example 1, and Comparative Example 2 is shown.
[0054] Figure 8 A graph showing the hot tack strength of Example 1, Comparative Example 1, and Comparative Example 2 is shown. DETAILED DESCRIPTION
[0055] Hereinafter, the present invention will be described in detail.
[0056] Olefin polymer film
[0057] The olefin polymer film according to one specific embodiment of the present invention is prepared by molding an olefin polymer.
[0058] In this case, the olefin polymer used for preparing the olefin polymer film according to one specific embodiment of the present invention may be prepared by polymerizing an olefin monomer in the presence of a catalyst.
[0059] Catalysts for the polymerization of olefins
[0060] In the preparation of the olefin polymer, especially linear low-density polyethylene, used for preparing the olefin polymer film according to a specific embodiment of the present invention, the catalyst used comprises at least one transition metal compound represented by the following Chemical Formula 1 and at least one co-catalyst compound.
[0061]
Chemical formula 1
[0062]
[0063] In the Chemical Formula 1, n is each independently an integer of 1 to 20, preferably an integer of 1 to 10, and more preferably an integer of 1 to 5. Specifically, n may be 1 or 2.
[0064] M is titanium (Ti), zirconium (Zr) or hafnium (Hf). Specifically, M may be zirconium or hafnium.
[0065] X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, C 6-20 Arylamide or C 1-20 Specifically, X can be halogen, or substituted or unsubstituted C 1-20 More specifically, each X may be chlorine, methyl or butyl.
[0066] R 1 To R 4 and R 5 To R 8 are each independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 In addition, R 1 To R 4 and R 5 To R 8 Each independently can form a substituted or unsubstituted saturated or unsaturated C 4-20 Specifically, R 1 To R 4 and R 5 To R 8 Each may be hydrogen.
[0067] R 9 To R 11 and R 12 To R 14 are each independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl.
[0068] Specifically, R 9 To R 11 and R 12 To R 14 Each may be substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 6-20 More specifically, R 9 To R 11 and R 12 To R 14 Each may be a methyl group or a phenyl group.
[0069] In a preferred embodiment of the present invention, the compound represented by the Chemical Formula 1 may be any one selected from the compounds represented by the following Chemical Formulas 1-1 to 1-8.
[0070]
[0071] In the chemical formulas 1-1 to 1-8, M is zirconium or hafnium, and X is each halogen, or a substituted or unsubstituted C 1-20 Alkyl is preferably chlorine, methyl or butyl, Me is methyl, and Ph is phenyl.
[0072] In a more preferred embodiment of the present invention, the compound represented by the Chemical Formula 1 may be any one selected from the compounds represented by the following Chemical Formulas 1-9 to 1-11.
[0073]
[0074] In the Chemical Formulae 1-9 to 1-11, Me is a methyl group, and Bu is an n-butyl group.
[0075] In addition, the co-catalyst compound may include one or more selected from the group consisting of a compound represented by the following Chemical Formula 2, a compound represented by the following Chemical Formula 3, and a compound represented by the following Chemical Formula 4.
[0076]
Chemical formula 2
[0077]
[0078] In the chemical formula 2, n may be an integer of 2 or more, R a Can be halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 Specifically, R a It may be methyl, ethyl, n-butyl or isobutyl.
[0079]
Chemical formula 3
[0080]
[0081] In the chemical formula 3, D is aluminum (Al) or boron (B), R b , R c and R d are independently a halogen atom, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon or C 1-20 Specifically, when D is aluminum, R b , R c and R d Each independently can be methyl or isobutyl. When D is boron, R b , R c and R d Each may be a pentafluorophenyl group.
[0082]
Chemical formula 4
[0083] [LH] + [Z(A)4] - or [L] + [Z(A)4] -
[0084] In the chemical formula 4, L is a neutral or cationic Lewis base, [LH] + and [L] + is a Bronsted acid ( nsted acid), Z is a Group 13 element, and A is each independently a substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Specifically, [LH] + It can be a dimethylanilinium cation, [Z(A)4] - Can be [B(C6F5)4] - , [L] + Can be [(C6H5)3C] + .
[0085] Specifically, the compound represented by the Chemical Formula 2 may be, for example, methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, and the like, and is preferably methylaluminoxane, but is not limited thereto.
[0086] The compound represented by the chemical formula 3 may be, for example, trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, tributylboron, and the like, and preferably trimethylaluminum, triethylaluminum, and triisobutylaluminum, but is not limited thereto.
[0087] The compound represented by the chemical formula 4 may be, for example, triethylammonium tetraphenylboron, tributylammonium tetraphenylboron, trimethylammonium tetraphenylboron, tripropylammonium tetraphenylboron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, N,N-diethylanilinium tetraphenylboron, N,N-diethylanilinium tetra(pentafluorophenyl)boron, diethylammonium tetra(pentafluorophenyl)boron, triphenylphosphonium tetraphenylboron, trimethyl ... ammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o-p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetra(pentafluorophenyl)aluminum, N,N-diethylanilinium tetraphenylaluminum, N,N-diethylanilinium tetra(pentafluorophenyl)aluminum, diethylammonium tetra(pentafluorophenyl)aluminum, triphenylphosphite tetraphenylaluminum, trimethylphosphite tetraphenylaluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o-p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron and triphenylcarbonium tetra(pentafluorophenyl)boron, etc.
[0088] In a preferred embodiment of the present invention, the catalyst for polymerizing olefins may further comprise a carrier supporting a transition metal compound. Specifically, the carrier may support a transition metal compound and a co-catalyst compound at the same time.
[0089] At this time, the surface of the carrier may include a substance containing a hydroxyl group, and it is preferred to use a substance that has been dried and the surface is dehydrated and has a highly reactive hydroxyl group and a siloxane group. For example, the carrier may include at least one selected from silicon dioxide, aluminum oxide and magnesium oxide. Specifically, silicon dioxide, silicon dioxide-aluminum oxide and silicon dioxide-magnesium oxide, etc. dried at high temperatures can be used as carriers, and they may generally contain oxides, carbonates, sulfates and nitrate components such as Na2O, K2CO3, BaSO4 and Mg(NO3). In addition, they may also include carbon, zeolite, magnesium chloride, etc. However, the carrier is not limited thereto, and is not particularly limited, as long as it can load transition metal compounds and co-catalyst compounds.
[0090] The average particle size of the carrier may be 10 μm to 250 μm, preferably 10 μm to 150 μm, and more preferably 20 μm to 100 μm.
[0091] The micropore volume of the carrier may be 0.1 cc / g to 10 cc / g, preferably 0.5 cc / g to 5 cc / g, and more preferably 1.0 cc / g to 3.0 cc / g.
[0092] The specific surface area of the carrier may be 1 m2 / g to 1,000 m2 / g, preferably 100 m2 / g to 800 m2 / g, and more preferably 200 m2 / g to 600 m2 / g.
[0093] In a preferred embodiment, when the carrier is silica, the drying temperature of the silica may be 200° C. to 900° C. The drying temperature may preferably be 300° C. to 800° C., more preferably 400° C. to 700° C. When the drying temperature is lower than 200° C., the moisture on the surface reacts with the promoter compound due to excessive moisture, and when the drying temperature exceeds 900° C., the structure of the carrier may collapse.
[0094] The concentration of hydroxyl groups in the dried silica may be 0.1 to 5 mmole / g, preferably 0.7 to 4 mmole / g, and more preferably 1.0 to 2 mmole / g. When the concentration of hydroxyl groups is less than 0.1 mmole / g, the loading amount of the co-catalyst compound may be reduced, and when the concentration of hydroxyl groups exceeds 5 mmole / g, the problem of deactivation of the catalyst component may occur.
[0095] The amount of the transition metal compound supported on the carrier may be 0.001 mmole to 1 mmole based on 1 g of the carrier. When the ratio of the transition metal compound to the carrier satisfies the above range, appropriate supported catalyst activity may be exhibited, thereby facilitating the maintenance of catalyst activity and economy.
[0096] The amount of the co-catalyst compound supported on the carrier may be 2 to 15 mmole based on 1 g of the carrier. When the ratio of the co-catalyst compound to the carrier satisfies the above range, it is beneficial to the maintenance of catalyst activity and economy.
[0097] One, two or more types of carriers can be used. For example, a transition metal compound and a co-catalyst compound can be loaded on one type of carrier, or a transition metal compound and a co-catalyst compound can be loaded on two or more types of carriers, respectively. In addition, only one of the transition metal compound and the co-catalyst compound can be loaded on the carrier.
[0098] The transition metal compound and / or the co-catalyst compound used in the catalyst for olefin polymerization may be loaded by a physical adsorption method or a chemical adsorption method.
[0099] For example, the physical adsorption method may be a method of bringing a solution containing a transition metal compound into contact with a carrier and then drying it; a method of bringing a solution containing a transition metal compound and a co-catalyst compound into contact with a carrier and then drying it; or a method of bringing a solution containing a transition metal compound into contact with a carrier and then drying it to prepare a carrier loaded with a transition metal compound, and also bringing a solution containing a co-catalyst compound into contact with a carrier and then drying it to prepare a carrier loaded with a co-catalyst compound, and then mixing them, etc.
[0100] The chemical adsorption method can be a method in which a co-catalyst compound is loaded on the surface of a carrier and then a transition metal compound is loaded on the co-catalyst compound; or a method in which a functional group on the surface of the carrier (for example, in the case of silica, a hydroxyl group (-OH) on the surface of silica) is covalently bonded to the catalyst compound.
[0101] Olefin polymers
[0102] The olefin polymer prepared by polymerizing an olefin monomer under the above-mentioned catalyst conditions for polymerizing olefin may be a homopolymer of the olefin monomer or a copolymer of the olefin monomer and a comonomer.
[0103] The olefin monomer may be selected from C 2-20 α-olefins, C 1-20 Diolefins, C 3-20 Cycloolefins and C 3-20 At least one of the cycloalkadiene.
[0104] For example, the olefin monomer may be ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene or 1-hexadecene, and the olefin polymer may be a homopolymer containing only one selected from the above exemplary olefin monomers, or a copolymer containing multiple selected from the above exemplary olefin monomers.
[0105] In an exemplary embodiment, the olefin polymer may be a polymer composed of ethylene and C 3-20 The copolymer is a copolymer obtained by copolymerizing α-olefins, and preferably a copolymer obtained by copolymerizing ethylene and 1-hexene, but is not limited thereto.
[0106] In this case, the ethylene content is preferably 55 to 99.9 wt%, more preferably 90 to 99.9 wt%.The α-olefin comonomer content is preferably 0.1 to 45 wt%, more preferably 0.1 to 10 wt%.
[0107] The olefin polymer according to the specific embodiment of the present invention may be polymerized by free radical, cationic, coordination, condensation, addition, etc. polymerization reactions, but is not limited thereto.
[0108] As an embodiment of the present invention, the olefin polymer may be prepared by gas phase polymerization, solution polymerization or slurry polymerization, etc. Preferably, the polymerization of the olefin monomer may be performed by gas phase polymerization, specifically, the polymerization of the olefin monomer may be performed in a gas phase fluidized bed reactor.
[0109] When the olefin polymer is prepared by solution polymerization or slurry polymerization, a solvent such as pentane, hexane, heptane, nonane, decane and isomers thereof may be used. 5-12 Aliphatic hydrocarbon solvents; aromatic hydrocarbon solvents such as toluene and benzene; hydrocarbon solvents substituted with chlorine atoms such as dichloromethane and chlorobenzene; and mixtures thereof, etc., but are not limited thereto.
[0110] The olefin polymer used to prepare the olefin polymer film according to the specific embodiment of the present invention satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 (2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60; and (3) the comonomer distribution slope (CDS) defined by the following mathematical formula 1 is 1 or more.
[0111] Specifically, the density of the olefin polymer may be 0.910 g / cm 3 Up to 0.940g / cm 3 Preferably, the density of the olefin polymer may be 0.910 g / cm 3 Up to 0.920g / cm 3 , or 0.915g / cm 3 Up to 0.925g / cm 3 .
[0112] In addition, the melt index (I) of the olefin polymer measured at 190°C under a load of 21.6 kg is 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60. Preferably, the MFR of the olefin polymer may be 20 to 50, or 20 to 40.
[0113] In addition, the comonomer distribution slope (CDS) of the olefin polymer, which is defined by the following Mathematical Formula 1, is 1 or more. Preferably, the CDS of the olefin polymer may be 2 to 5, or 2 to 4.
[0114]
Mathematical formula 1
[0115]
[0116] In the above mathematical formula 1, C 20 and C 80 are the comonomer contents corresponding to the cumulative mass fractions of 20% and 80% in the comonomer distribution, M 20 and M 80 They are the molecular weights corresponding to the cumulative mass fractions of the comonomer distribution reaching 20% and 80%, respectively.
[0117] Among them, by using GPC-FTIR equipment, the comonomer distribution of olefin polymers can be continuously measured together with the molecular weight and molecular weight distribution of the polymer.
[0118] The CDS of olefin polymers shows the slope of the comonomer content relative to the molecular weight when the cumulative mass fraction reaches 20% and 80% in the comonomer distribution diagram. As the CDS of olefin polymers increases, the comonomers are concentrated in the polymer chains with high molecular weight, thus having excellent mechanical strength and heat sealing properties.
[0119] Olefin polymer film
[0120] The olefin polymer film according to one specific embodiment of the present invention may be prepared by molding the above-mentioned olefin polymer.
[0121] The olefin polymer film according to the specific embodiment of the present invention has excellent mechanical properties and heat sealability by including the above-mentioned olefin polymer. The above-mentioned olefin polymer olefin polymer has a relatively wide molecular weight distribution, and there are relatively more short chain branches in the high molecular weight component, so it can be understood that the olefin polymer film made therefrom has excellent mechanical strength and low-temperature heat sealability.
[0122] Specifically, the olefin polymer film according to one embodiment of the present invention satisfies: the heat seal strength measured according to ASTM F88 at 0.2 bar, 1.5 seconds and 125° C. is 90 gf / 2.5 cm or more, preferably 90 to 200 gf / 2.5 cm, and more preferably 90 to 180 gf / 2.5 cm. Specifically, the olefin polymer film according to one embodiment of the present invention satisfies: the heat seal strength measured according to ASTM F88 at 0.2 bar, 1.5 seconds and 140° C. is 210 gf / 2.5 cm or more, preferably 210 to 250 gf / 2.5 cm, and more preferably 210 to 230 gf / 2.5 cm.
[0123] In addition, the olefin polymer film according to one specific embodiment of the present invention satisfies: the hot tack strength at 95°C measured according to ASTM F1921 is 0.5 N / 2 cm or more, preferably 0.5 to 3.5 N / 2 cm, more preferably 0.5 to 2.0 N / 2 cm. The olefin polymer film according to one specific embodiment of the present invention satisfies: the hot tack strength at 110°C measured according to ASTM F1921 is 3.5 N / 2 cm or more, preferably 3.5 to 7.5 N / 2 cm, more preferably 3.5 to 5.0 N / 2 cm.
[0124] In addition, the olefin polymer film according to one embodiment of the present invention may have a haze of 10% or less measured according to ASTM D 1003 after being formed into a thickness of 50 μm. Preferably, the olefin polymer film according to one embodiment of the present invention may have a haze of 7% or less, or 6% or less.
[0125] The olefin polymer film according to the specific embodiment of the present invention can be effectively used as a stretch film, a laminating film, a plastic film, a silage film, an agricultural film, and the like.
[0126] Method for preparing olefin polymer film
[0127] In a specific embodiment, the present invention provides a method for preparing an olefin polymer film, the method comprising: step (a), polymerizing olefin monomers in the presence of a catalyst comprising at least one transition metal compound represented by the following chemical formula 1 and at least one co-catalyst compound to obtain an olefin polymer; and step (b), molding the olefin polymer to obtain a film, wherein the olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 , preferably 0.910g / cm 3 Up to 0.920g / cm 3(2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60, preferably 20 to 40; and (3) the comonomer distribution slope (CDS) defined by the following mathematical formula 1 is 1 or more, preferably 2 to 5, the heat sealing strength of the olefin polymer film measured at 0.2 bar, 1.5 seconds and 125°C is 90 gf / 2.5 cm or more, preferably 90 to 200 gf / 2.5 cm, and the heat sealing strength measured at 0.2 bar, 1.5 seconds and 140°C is 210 gf / 2.5 cm or more, preferably 210 to 250 gf / 2.5 cm.
[0128]
Chemical formula 1
[0129]
[0130]
Mathematical formula 1
[0131]
[0132] In the chemical formula 1, n, M, X and R 1 To R 14 , and C in the above mathematical formula 1 20 , C 80 、M 20 and M 80 Same as above definition.
[0133] In the step (a), the olefin polymer may be prepared by gas phase polymerization, solution polymerization or slurry polymerization, etc. Preferably, the polymerization of the olefin monomer may be performed by gas phase polymerization, specifically, the polymerization of the olefin monomer may be performed in a gas phase fluidized bed reactor.
[0134] In addition, in the step (a), the olefin polymer can be prepared by copolymerizing an olefin monomer and an olefin comonomer. In this case, the olefin monomer is ethylene, and the olefin comonomer can be selected from one or more of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene and 1-hexadecene. Preferably, the olefin monomer is ethylene, and the olefin comonomer is 1-hexene.
[0135] In the step (b), the method for preparing the olefin polymer film according to the specific embodiment of the present invention is not particularly limited, and methods known in the technical field to which the present invention belongs can be used. For example, the above-mentioned olefin polymer can be processed by conventional methods such as blown film molding, extrusion molding, and cast molding to prepare the olefin polymer film. Among them, blown film molding is the most preferred.
[0136] The olefin polymer film prepared by the method for preparing an olefin polymer film according to a specific embodiment of the present invention satisfies: the 95°C hot tack strength measured in accordance with ASTM F19 21 is 0.5 N / 2 cm or more, preferably 0.5 to 3.5 N / 2 cm, more preferably 0.5 to 2.0 N / 2 cm, and the 110°C hot tack strength is 3.5 N / 2 cm or more, preferably 3.5 to 7.5 N / 2 cm, more preferably 3.5 to 5.0 N / 2 cm.
[0137] Example
[0138] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples are only used to describe the present invention, and the scope of the present invention is not limited thereto.
[0139] [Preparation Example 1] Preparation of bis[(2-trimethylsilylmethy lallyl)cyclopentadienyl]hafnium dichloride (Chemical Formula 1-9)
[0140] 2-(trimethylsilylmethyl)-2-propen-1-ol Preparation of 1-ol
[0141] To a solution obtained by dissolving 2-(trimethylsilylmethyl)allylacetate (2.69 g, 14.4 mmol) in methanol (22 mL), potassium carbonate (K2CO3) aqueous solution (6.6 M, 14.4 mmol) was slowly added. After the addition was completed, it was stirred at room temperature for 4 hours. After stirring, water was added thereto to terminate the reaction. After the organic layer was extracted with diethyl ether, the residual water was removed by using magnesium sulfate (MgSO4). All solvents were removed under vacuum conditions to obtain 1.51 g (72%) of a light yellow oil compound.
[0142] 1 H-NMR (CDCl3, 300MHz): δ4.90-4.88 (m, 1H), 4.66 (s, 1H), 3.97 (s, 2H), 1.53 (s, 2H), 0.03 (s, 9H).
[0143] 2-(trimethylsilylmethyl) methanesulfonate Preparation of methanesulfonate
[0144] To a solution obtained by diluting 2-(trimethylsilylmethyl)-2-propene-1-ol (1.51 g, 10.5 mmole) and triethylamine (1.91 g, 18.8 mmole) in dichloromethane (30 ml), methanesulfonyl chloride (1.8 g, 15.7 mmole) was slowly added at 0°C. Then, stirring was performed for 3 hours at 0°C. After adding an aqueous sodium bicarbonate (NaHCO3) solution at 0°C to terminate the reaction, the organic layer was extracted and separated by using dichloromethane. After removing the residual water by using sodium sulfate (Na2SO4), all the solvents were removed under vacuum to obtain 1.9 g (82%) of a yellow oil compound.
[0145] 1 H-NMR (CDCl3, 300MHz): δ 5.03 (d, 1H), 4.84 (s, 1H), 4.56 (s, 2H), 3.02 (s, 3H), 1.60 (s, 2H), 0.06 (s, 9H).
[0146] 2-(trimethylsilylmethyl)allyl bromide Preparation
[0147] To a solution obtained by diluting 2-(trimethylsilylmethyl)methanesulfonate (1.9 g, 8.54 mmol) in tetrahydrofuran (20 mL), a solution in which lithium bromide was dispersed in tetrahydrofuran (15 mL) was slowly added at room temperature, followed by stirring at 110° C. for 4 hours. After adding distilled water at 0° C. to terminate the reaction, the organic layer was extracted and separated with diethyl ether. After removing the remaining water with sodium sulfate, all the solvents were removed under vacuum to obtain 1.12 g (65%) of a yellow oily compound.
[0148] 1 H-NMR (CDCl3, 300MHz): δ5.04 (s, 1H), 4.74 (d, 1H), 3.90 (d, 2H), 1.72 (d, 2H), 0.05 (s, 9H).
[0149] [2-(cyclopentadienylmethyl)allyl]trimethylsilane Preparation of allyl]trimethylsilane
[0150] To a solution obtained by diluting 2-(trimethylsilylmethyl)allyl bromide (1.12 g, 5.41 mmol) in tetrahydrofuran (20 ml), sodium cyclopentadienide (3.04 g, 6.49 mmol, 2M in THF) was slowly added dropwise at -30°C, and then the temperature was slowly raised to room temperature and stirred for 12 hours. After adding distilled water at 0°C to terminate the reaction, the organic layer was extracted and separated by using diethyl ether. After removing the remaining water by using magnesium sulfate, 620 mg (60%) of a light yellow oily compound was obtained by separation by using column chromatography (hexane).
[0151] 1 H-NMR (CDCl3, 300MHz): δ6.42-6.02(m,4H), 4.60-4.55(m,2H), 3.06-2.97(m,2H), 2.87-2.85(m,2H), 1.54(s,2H), 0.03(d,9H).
[0152] [2-(trimethylsilylmethyl)allyl]cyclopentadienyllithium Preparation of allyl]cyclopentadienyl lithium
[0153] To a solution obtained by diluting [2-(cyclopentadienylmethyl)allyl]trimethylsilane (620 mg, 3.22 mmole) in tetrahydrofuran (10 ml), n-butyl lithium (1.44 g, 2.93 mmole, 1.6 M hexane solution) was slowly added at -30 ° C, and then the temperature was slowly raised to room temperature and stirred for 12 hours. After the solvent of the reaction solution was dried under vacuum, hexane was added and stirred for 15 minutes. The generated solid was filtered and dried under vacuum to obtain 528 mg (83%) of a light yellow solid compound.
[0154] Preparation of Bis[(2-trimethylsilylmethylallyl)cyclopentadienyl]Hafnium Dichloride
[0155] To a solution obtained by diluting [2-(trimethylsilylmethyl)allyl]cyclopentadienyl lithium (280 mg, 1.41 mmole) in toluene (3 ml), a solution of hafnium chloride (HfCl4; 226 mmole, 0.71 mmole) dispersed in toluene (2 ml) was slowly added at -30°C, and then the temperature was slowly raised to room temperature and stirred for 12 hours. When the reaction was completed, the reaction solution was filtered, and the solvent of the filtrate was dried under vacuum. The generated solid was washed with hexane and then dried to obtain 180 mg (41%) of a white solid compound.
[0156] 1H-NMR (CDCl3, 300MHz): δ6.21(t,2H), 6.12(t,2H), 4.54(d,2H), 4.44(d,1H), 3.28(s,2H), 1.52(s,2H), 0.05(s,9H).
[0157] Preparation of supported metallocene catalysts
[0158] 624 g of a 10% toluene solution of methylaluminoxane was added to 4.15 g of the compound represented by Chemical Formula 1-9, and then stirred at room temperature for 1 hour. The solution after the reaction was added to 140 g of silica (XPO-2402), to which 3 liters of toluene were further added, and stirred at 70° C. for 2 hours. The loaded catalyst was washed with 1 liter of toluene and dried overnight at 60° C. under vacuum conditions to prepare 200 g of a supported catalyst in powder form.
[0159] [Preparation Example 2] Preparation of dimethyl bis[(2-trimethyl silylmethylallyl)cyclopentadienyl]hafnium (chemical formula 1-10)
[0160] To a solution obtained by diluting bis[2-(trimethylsilylmethyl)allyl]cyclopentadienyl hafnium dichloride (2.4 g, 3.79 mmole) obtained in Preparation Example 1 in toluene, MeMgBr (3.0 M diethyl ether solution, 11.4 mmole) was slowly added at -30°C, and the temperature was slowly raised to room temperature and stirred for 12 hours. When the reaction was completed, extraction was performed with toluene and filtration was performed, and then the solvent of the filtrate was dried under vacuum. The generated solid was washed with hexane and dried to obtain 2.08 g (93%) of a white solid compound.
[0161] 200 g of a supported catalyst was prepared in the same manner as in Preparation Example 1 using 3.87 g of the compound represented by Chemical Formula 1-10.
[0162] [Preparation Example 3] Preparation of dibutyl bis[(2-trimethylsilylmethylallyl)cyclopentadienyl]hafnium (chemical formula 1-11)
[0163] To a solution obtained by diluting bis[2-(trimethylsilylmethyl)allyl]cyclopentadienyl hafnium dichloride (4 g, 6 mmol e) obtained in Preparation Example 1 in toluene (100 ml), n-butyl lithium (5.5 g, 13 mmole) was slowly added at -30°C, and then the temperature was slowly raised to room temperature and stirred for 12 hours. When the reaction was completed, the reaction solution was filtered, and the solvent of the filtrate was dried under vacuum to obtain 3.4 g (80%) of a yellow liquid compound.
[0164] 200 g of a supported catalyst was prepared in the same manner as in Preparation Example 1 using 4.43 g of the compound represented by Chemical Formula 1-11.
[0165] [Example 1 to Example 3]
[0166] The ethylene / 1-hexene copolymer was prepared by using a gas phase fluidized bed reactor and under the conditions of the supported catalysts respectively obtained in Preparation Examples 1 to 3. The ethylene partial pressure in the reactor was maintained at about 15 kg / cm 3 , the polymerization temperature is maintained at 80°C to 90°C.
[0167] The polymerization conditions of the above examples are shown in Table 1 below.
[0168]
Table 1
[0169]
[0170] [Comparative Example 1 to Comparative Example 2]
[0171] Hanwha Chemical's linear low-density polyethylene M1810HN (density 0.918 g / cm 3 , melt index is 1.0g / 10min) and M2010HN (density is 0.920g / cm 3 , melt index is 1.0 g / 10 min) for comparison.
[0172] [Experimental Example]
[0173] The physical properties of the olefin polymers of the above examples were measured according to the following methods and standards. The results are shown in Table 2 below.
[0174] (1) Melt index and melt index ratio (MFR)
[0175] According to ASTM D 1238, the melt index was measured at 190°C under 21.6 kg load and 2.16 kg load, and the ratio (MI 21.6 / MI 2.16 ).
[0176] (2) Density
[0177] The measurement was carried out according to ASTM D1505.
[0178] (3) Comonomer distribution slope (CDS)
[0179] The measurement was performed by using gel permeation chromatography-FTIR (GPC-FTIR).
[0180]
Table 2
[0181]
[0182] The resins of Examples 1 to 3 and Comparative Examples 1 to 2 were respectively prepared into films with a thickness of 50 μm by a 40 mm blown film extruder (screw diameter of 40 mm, die diameter of 75 mm, die gap of 2 mm). At this time, the extrusion conditions were C1 / C2 / C3 / A / D1 / D2=160 / 165 / 170 / 175 / 180 / 180°C, the screw speed was fixed at 80 rpm, and the blow-up ratio (BUR) was fixed at 2.
[0183] The physical properties of the olefin polymer films of Example 1 and Comparative Examples 1 to 2 were measured according to the following methods and standards. The results are shown in Table 3 below.
[0184] (5) Melting temperature
[0185] The melting point of the polymer was measured using a differential scanning calorimeter (DSC, equipment name: DSC 2920, manufacturer: TA Instrument). Specifically, the polymer was heated to 200°C and kept at this temperature for 5 minutes, then cooled to 20°C and heated again, at which time, the temperature increase rate and decrease rate were both adjusted to 20°C / min.
[0186] (6) Haze
[0187] The film was molded to a thickness of 50 μm and measured in accordance with ASTM D 1003. At this time, each test piece was measured 5 times and the average value was taken.
[0188] (7) Transparency
[0189] The film was molded to a thickness of 50 μm and measured in accordance with ASTM D 1003. At this time, each test piece was measured 5 times and the average value was taken.
[0190] (8) Heat seal strength
[0191] The measurement was carried out according to ASTM F88.
[0192] (9) Hot tack strength
[0193] The measurement was performed according to ASTM F1921.
[0194]
Table 3
[0195] unit Example 1 Comparative Example 1 Comparative Example 2 <![CDATA[I 2.16 ]]> (g / 10min) 1.0 1.08 1.0 MFR - 22.2 16 33.2 CDS - 3.29 0.07 0.01 density <![CDATA[(g / cm 3 )]]> 0.9180 0.9182 0.9202 Melting temperature (℃) 119.3 117.2 108.3 Haze % 5.45 8.72 4.66 transparency % 99.6 98.0 99.3 Heat seal strength (0.2 bar, 1.5 seconds, 125°C) (gf / 2.5cm) 93.06 2.16 5.22 Heat seal strength (0.2 bar, 1.5 seconds, 140°C) (gf / 2.5cm) 217.3 190.4 160.18 Hot tack strength (95°C) (N / 2㎝) 0.657 0.307 0.280 Hot tack strength (110℃) (N / 2㎝) 3.813 3.133 1.727
[0196] Industrial Applicability
[0197] The olefin polymer film according to the specific embodiment of the present invention, specifically the linear low-density polyethylene film, is easy to prepare and has excellent mechanical strength and heat sealing properties, especially low-temperature heat sealing properties.
Claims
1. An olefin polymer film, formed by molding an olefin polymer, in, The olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 (2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60; and (3) the comonomer distribution slope (CDS) defined by the following mathematical formula 1 is 1 or more, The olefin polymer film has a heat seal strength of 90 gf / 2.5 cm or more measured at 0.2 bar, 1.5 seconds and 125° C., and a heat seal strength of 210 gf / 2.5 cm or more measured at 0.2 bar, 1.5 seconds and 140° C., 【Mathematical formula 1】 In the above mathematical formula 1, C 20 and C 80 are the comonomer contents corresponding to the cumulative mass fractions of 20% and 80% in the comonomer distribution, M 20 and M 80 are the molecular weights corresponding to the cumulative weight fractions of 20% and 80% in the comonomer distribution, The olefin polymer is prepared by polymerizing olefin monomers in the presence of a catalyst, wherein the catalyst comprises at least one transition metal compound represented by the following Chemical Formula 1 and at least one co-catalyst compound, 【Chemical formula 1】 In the chemical formula 1, n is each independently an integer from 1 to 20, M is titanium, zirconium or hafnium, X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, C 6-20 Arylamide or C 1-20 Alkylene, R 1 To R 4 and R 5 To R 8 are each independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, R 9 To R 11 and R 12 To R 14 are each independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, R 1 To R 4 and R 5 To R 8 Each independently can form a substituted or unsubstituted saturated or unsaturated C 4-20 ring.
2. The olefin polymer film according to claim 1, characterized in that The olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.920g / cm 3 ; (2) MFR of 20 to 40; and (3) CDS of 2 to 5.
3. The olefin polymer film according to claim 1, characterized in that The co-catalyst compound is selected from the group consisting of the compound represented by the following Chemical Formula 2, the compound represented by the following Chemical Formula 3, and the compound represented by the following Chemical Formula 4, 【Chemical formula 2】 【Chemical formula 3】 【Chemical formula 4】 [L-H] + [Z(A)4] - or [L] + [Z(A)4] - , In the chemical formula 2, n is an integer of 2 or more, R a For halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 Hydrocarbon, In the chemical formula 3, D is aluminum or boron, R b , R c and R d are independently a halogen atom, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon or C 1-20 Alkoxy, In the chemical formula 4, L is a neutral or cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and A is each independently a substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 alkyl.
4. The olefin polymer film according to claim 1, characterized in that The catalyst further comprises a carrier supporting a transition metal compound and a promoter compound.
5. The olefin polymer film according to claim 1, characterized in that The olefin polymer is a copolymer of an olefin monomer and an olefin comonomer.
6. The olefin polymer film according to claim 5, characterized in that The olefin monomer is ethylene, and the olefin comonomer is one or more substances selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene and 1-hexadecene.
7. The olefin polymer film according to claim 6, characterized in that The olefin polymer is a linear low density polyethylene, wherein the olefin monomer is ethylene and the olefin comonomer is 1-hexene.
8. The olefin polymer film according to claim 1, characterized in that The olefin polymer has a 95° C. hot tack strength of 0.5 N / 2 cm or more, and a 110° C. hot tack strength of 3.5 N / 2 cm or more.
9. The olefin polymer film according to claim 1, characterized in that The olefin polymer film has a haze of 10% or less when measured after being formed into a thickness of 50 μm.
10. The olefin polymer film according to claim 1, characterized in that The olefin polymer film is one selected from a stretch film, a laminated film, a plastic film and an agricultural film.
11. A method for preparing an olefin polymer film, the method comprising: Step (a), polymerizing olefin monomers in the presence of a catalyst comprising at least one transition metal compound represented by the following Chemical Formula 1 and at least one co-catalyst compound to obtain an olefin polymer; as well as Step (b), forming the olefin polymer into a film, Wherein, the olefin polymer satisfies: (1) a density of 0.910 g / cm 3 Up to 0.940g / cm 3 (2) Melt index (I) measured at 190°C with a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (MFR) is 10 to 60; and (3) the comonomer distribution slope (CDS) defined by the following mathematical formula 1 is 1 or more, The olefin polymer film has a heat seal strength of 90 gf / 2.5 cm or more measured at 0.2 bar, 1.5 seconds and 125° C., and a heat seal strength of 210 gf / 2.5 cm or more measured at 0.2 bar, 1.5 seconds and 140° C., 【Chemical formula 1】 【Mathematical formula 1】 In the chemical formula 1, n, M, X and R 1 To R 14 As described in claim 1, C in the mathematical formula 1 20 , C 80 、M 20 and M 80 As described in claim 1.
12. The method for preparing an olefin polymer film according to claim 11, characterized in that: In step (a), the polymerization of the olefin monomers is performed by gas phase polymerization.
13. The method for preparing an olefin polymer film according to claim 12, characterized in that: In step (a), the polymerization of olefin monomers is carried out in a gas phase fluidized bed reactor.
14. The method for preparing an olefin polymer film according to claim 11, characterized in that: In step (a), an olefin polymer is prepared by copolymerizing an olefin monomer and an olefin comonomer, The olefin monomer is ethylene, and the olefin comonomer is one or more substances selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene and 1-hexadecene.
15. The method for preparing an olefin polymer film according to claim 14, characterized in that: The olefin monomer is ethylene, and the olefin comonomer is 1-hexene.
16. The method for preparing an olefin polymer film according to claim 11, characterized in that: The olefin polymer film has a 95° C. hot tack strength of 0.5 N / 2 cm or more, and a 110° C. hot tack strength of 3.5 N / 2 cm or more.
Citation Information
Patent Citations
Multi reactor solution polymerization, polyethylene and polyethylene film
CA2964562A1
Ethylene copolymer compositions, film and polymerization processes
CN104918972A
Polyethylene blend compositions and film
CN104937025A
Multi reactor solution polymerization, polyethylene and polyethylene film
US20180305530A1